2021
DOI: 10.3389/fpubh.2021.686122
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin Microencapsulation in Emulsion Paint Binder and Its Long-Term Efficacy Against Dengue Vector Aedes aegypti

Abstract: Various control interventions have been effective in the control of arthropod vectors to a certain extent; still, sustained vector control is an existing problem globally. Insecticide-based formulations have been found to be useful, however the proper delivery of active molecules to target vectors is important. Currently, synthetic pyrethroid deltamethrin (DM) has been microencapsulated in the emulsion paint binder and evaluated for long-term effectiveness against dengue vector Aedes aegypti. Different composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In an earlier study it was observed that cytoplasmic vacuolization was associated with deltamethrin-mediated initial changes, which resulted in autophagy and apoptosis ( Gutiérrez et al, 2016 ). The toxic effect of deltamethrin may not necessarily be due to direct toxicity ( Gondhalekar et al, 2013 ; Acharya et al, 2021 ) but deltamethrin exposure may result in excito-repellency ( Dhiman et al, 2021 ), homeostasis imbalance in the midgut thereby reducing the ability to digest food for nutrients ( Huang et al, 2015 ), dysregulation of the breathing activities ( Unkiewicz-Winiarczyk and Gromysz -K, 2012 ) and also limiting in the production of signaling molecules that regulate its own physiology ( Caccia et al, 2019 ). Deltamethrin was detected on the body surface of cockroach but not found in brain, ovary and gut tissue using HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study it was observed that cytoplasmic vacuolization was associated with deltamethrin-mediated initial changes, which resulted in autophagy and apoptosis ( Gutiérrez et al, 2016 ). The toxic effect of deltamethrin may not necessarily be due to direct toxicity ( Gondhalekar et al, 2013 ; Acharya et al, 2021 ) but deltamethrin exposure may result in excito-repellency ( Dhiman et al, 2021 ), homeostasis imbalance in the midgut thereby reducing the ability to digest food for nutrients ( Huang et al, 2015 ), dysregulation of the breathing activities ( Unkiewicz-Winiarczyk and Gromysz -K, 2012 ) and also limiting in the production of signaling molecules that regulate its own physiology ( Caccia et al, 2019 ). Deltamethrin was detected on the body surface of cockroach but not found in brain, ovary and gut tissue using HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-encapsulation of active ingredients in a polymeric matrix is another development of a controlled released delivery system of insecticides reported to have residual efficacy against cockroaches and some crawling insects [ 12 , 20 ]. The novel advancement of paint formulation by imbedding microencapsulated insecticide into latex paint offers a prolonged residual effect as compared to earlier insecticide paint (IP) products [ 21 , 22 ]. In these paints, the AIs slowly migrate to the substrate surface as the paint dries, meaning the insecticide is usable for a prolonged time.…”
Section: Introductionmentioning
confidence: 99%
“…Semi‐volatile pyrethroids are among the active ingredients used in formulated insecticidal paint products, combining the benefits of insect repellency and mortality 3,4 . Field‐realistic investigations have demonstrated product efficacy in indoor and outdoor settings against targeted insect populations 5–7 . Labelled as a ‘ready‐to‐use’ product, paint formulations can contain single or multiple active ingredients from different insecticide classes, including organophosphates, carbamates, insect growth regulators, and pyrethroids 8…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Field-realistic investigations have demonstrated product efficacy in indoor and outdoor settings against targeted insect populations. [5][6][7] Labelled as a 'ready-to-use' product, paint formulations can contain single or multiple active ingredients from different insecticide classes, including organophosphates, carbamates, insect growth regulators, and pyrethroids. 8 Transfluthrin (CAS: 118712-89-3; TFL) is a 4th generation, polyfluorobenzyl pyrethroid, which was first synthesized in 1976 as a 'hygiene knock-down insecticide.'…”
Section: Introductionmentioning
confidence: 99%